Analysis of Pitch Angle Control in Wind Energy Conversion Systems with Different Control Techniques - Percin, Hasan Bektas; Caliskan, Abuzer (Institute of Electrical and Electronics Engineers Inc., 2021)
In conversion systems used to produce electrical energy from the wind, the instant controls performed according to the instant wind speeds are crucial for stable and long working operations. One of these controls, pitch angle control is a type of control used for preventing damage to the system by activating at high wind speeds. In this study, pitch angle controls using PID and fuzzy logic were modelled in Matlab/Simulink environment and comparative analyzes were performed. © 2021 IEEE.
Rüzgar Enerjisi Dönüsüm Sistemlerinde Kanat Acisi Kontrolünün Farkli Kontrol Teknikleriyle Analizi
2021 Innovations in Intelligent Systems and Applications Conference, ASYU 2021 -- 6 October 2021 through 8 October 2021 -- Elazig -- 174400
Keywords: Fuzzy logic; Matlab/Simulink; Pitch angle; Wind energy